2007
DOI: 10.1038/sj.eye.6702902
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order wavefront aberration and letter-contrast sensitivity in keratoconus

Abstract: Aims To evaluate the relation between higher-order aberration of the eye and contrast sensitivity function in eyes with keratoconus. Methods In 22 eyes of 14 patients with keratoconus (age 30.578.4 years, means7SD) and 26 eyes of 13 normal controls (age 29.276.7 years), ocular higher-order wavefront aberration for a 6-mm pupil was measured with the Hartmann-Schack aberrometer (KR-9000 PW, Topcon). The root mean square (RMS) of third-and fourth-order Zernike coefficients was used to represent higher-order aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
4
23
4
3
Order By: Relevance
“…We found that higher order aberrations (HOAs) were larger in this same cohort of keratoconus and keratoconus suspect eyes compared with those in normal eyes, 15 and there may also be an association between contrast sensitivity and HOAs. 16 Our findings reinforce the opinion of some researchers that the measurement of high-contrast VA alone does not adequately describe visual function 17 and that factors such as contrast sensitivity and HOAs may explain why patients in clinical practice seem to experience functional difficulties disproportionate to their documented VA. The Collaborative Longitudinal Evaluation of Keratoconus (CLEK) study, for example, found that their patients were experiencing deficits in vision-related quality of life on par with the patients with age-related macular degeneration, despite the fact that the majority (94%) of their study patients demonstrated binocular, high-contrast VA of 20/40 or better.…”
Section: Discussionsupporting
confidence: 89%
“…We found that higher order aberrations (HOAs) were larger in this same cohort of keratoconus and keratoconus suspect eyes compared with those in normal eyes, 15 and there may also be an association between contrast sensitivity and HOAs. 16 Our findings reinforce the opinion of some researchers that the measurement of high-contrast VA alone does not adequately describe visual function 17 and that factors such as contrast sensitivity and HOAs may explain why patients in clinical practice seem to experience functional difficulties disproportionate to their documented VA. The Collaborative Longitudinal Evaluation of Keratoconus (CLEK) study, for example, found that their patients were experiencing deficits in vision-related quality of life on par with the patients with age-related macular degeneration, despite the fact that the majority (94%) of their study patients demonstrated binocular, high-contrast VA of 20/40 or better.…”
Section: Discussionsupporting
confidence: 89%
“…Contrast sensitivity generally demonstrates a better correlation than Snellen acuity with HOAs. 19,20 Given the high levels of posterior aberrations in DSAEK corneas, it is possible that these HOAs may have a role in degrading postoperative visual acuity, which was previously attributed solely to the interface.…”
Section: Visual Acuity Correlationmentioning
confidence: 98%
“…12,17 Even if the corrected visual acuity is good, CS can be decreased in patients with keratoconus due to higher-order aberrations. 18,19 Vertical coma is the most dominant higherorder aberration in eyes with keratoconus. 20 Caporossi et al 21 reported a significant improvement of coma after CXL.…”
Section: Discussionmentioning
confidence: 99%